Motivation for Pregnant Women to Get Covid-19 Vaccination - Sukmawati, Ellyzabeth; Imanah, Norif Didik Nur (Jurnal Bidan Cerdas, 2024)
Introduction: In Indonesia, the uptake of COVID-19 vaccines has emerged as a divisive topic, sparking debate and controversy among the population. Despite government efforts to promote vaccination, the acceptance rate remains low in certain regions. For instance, in Central Java, only approximately 60% of pregnant women have been vaccinated against COVID-19, well below the national target of 80%. This lack of acceptance is largely due to misinformation, fear, and the lack of knowledge within the community, exacerbated by insufficient government oversight in vaccination campaigns. As a result, pregnant women have displayed varying levels of hesitancy and concern, which influences their response to the COVID-19 vaccine Methods: This type of study quantitativeand involved pregnant woman conducted across Central Java. A total of participants is 1084 person and duration two year in 2022-2024th. Data were collected through primarry and secondary data. Data analysis using multiple linear regression and R-Square test. Ethical approval was obtained from research and community service STIKES Serulingmas instituation and participants provided Informed consent. Results:  The motivation of pregnant women has a positive and significant direct effect on the interest in vaccination with ρѵ = 0.000 <0.05, meaning that the better the mother's motivation. The coefficient value of 78.3% has an effect on interest in vaccination against Covid-19. Conclusion:  Motivation of pregnant women influences interest in vaccination. The extent of societal unease and skepticism leading to misconceptions about COVID-19 immunization.